2023
DOI: 10.2147/ppa.s396383
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Social Capital and Hypertension Among Type 2 Diabetes Mellitus Patients: The Moderating Effect of Depressive Symptoms

Abstract: Purpose This study aimed to evaluate the relationship between social capital (SC) and hypertension among type 2 diabetes mellitus (T2DM) patients, considering the moderation effects of depressive symptoms. Patients and Methods A total of 1761 Chinese T2DM patients completed measure scales of social capital and epidemiological survey depression scale (CES-D). The Bootstrap methods PROCESS program is employed to test the moderation model. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A Qualitative Study. 1 We congratulate the authors for the results of their research which saw a very valuable relationship in the world of health which provides information on how Social Capital influences Type 2 Diabetes Mellitus (T2DM) patients and its impact on early symptoms of depression. This research is the latest breakthrough that combines two disciplines, namely internal medicine and psychology.…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations
“…A Qualitative Study. 1 We congratulate the authors for the results of their research which saw a very valuable relationship in the world of health which provides information on how Social Capital influences Type 2 Diabetes Mellitus (T2DM) patients and its impact on early symptoms of depression. This research is the latest breakthrough that combines two disciplines, namely internal medicine and psychology.…”
Section: Dear Editormentioning
confidence: 99%
“…Ning Yan et al in their research found an inverse relationship between Social Capital and depressive symptoms, Social Capital and hypertension, and a positive relationship between depressive symptoms and hypertension. 1 Researchers also provide evidence that depressive symptoms moderate the relationship between Social Capital and hypertension. However, we need to know that income, diabetes duration, sleep duration, pain pressure, health self-assessment, and glycemic control directly affect depression in Type 2 Diabetes Mellitus patients, while age, frequency of blood glucose monitoring, and glycemic control awareness exercises have a direct effect indirect.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension, commonly known as high blood pressure, is characterized by elevated systemic arterial pressure, while diabetes mellitus is a metabolic disorder characterized by chronic hyperglycemia resulting from insulin resistance or insufficient insulin production. (Haile et al, 2023;Malikovna & Erkinovna, 2023;Yan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%